Age, Body Mass Index, Physical Activity and Quality of Life in Turkish Pregnant Woman with and Without a Diagnosis of Gestational Diabetes Mellitus: A Comparative Study - Tayyar, Yaren Nur; Kahyaoglu Sut, Hatice (Makara Journal of Health Research, 2023)
Background: This study aimed to examine and compare the age, body mass index (BMI), physical activity (PA), and quality of life (QOL) of third-trimester Turkish pregnant women with and without a diagnosis of gestational diabetes mellitus (GDM). Methods: A comparative study was conducted in the obstetrics clinic of a university hospital in Turkey, and it included 210 women (GDM women = 105 and non-GDM women = 105). Personal Information Form, International Physical Activity Questionnaire-Short Form (IPAQ), and World Health Organization Quality of Life-Short Form-Turkish (WHOQOL-Bref-TR) were used. Results: The age and BMI of GDM women were higher than those of non-GDM (p < 0.05). The results show that non-GDM women in their third trimester had higher scores on the WHOQOL-Bref-TR domains compared with those with GDM (p < 0.05). Among GDM women, a significant positive correlation was observed among WHOQOL-Bref-TR psychological (r = 0.77, p < 0.05) and environmental (r = 0.85, p < 0.05) domains and moderate IPAQ scores. A moderate positive correlation was detected among physical, psychological, social relations, environmental domains of WHOQOL-Bref-TR, and walking and total score in IPAQ (r = 0.39–0.54, p < 0.05). Conclusions: Local health policies should focus on community education programs, such as regular PA based on BMI and age, for the positive QOL of GDM women.